2022
DOI: 10.3389/fmicb.2022.952473
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface microbiota: Ophthalmic infectious disease and probiotics

Abstract: Recently, increasing studies have emphasized the importance of commensal bacteria in humans, including microbiota in the oral cavity, gut, vagina, or skin. Ocular surface microbiota (OSM) is gaining great importance as new methodologies for bacteria DNA sequencing have been published. This review outlines the current understanding and investigation of OSM and introduces the new concept of the gut–eye axis. Moreover, we have collected current studies that focus on the relationship between ophthalmic infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 105 publications
(94 reference statements)
0
16
0
1
Order By: Relevance
“…The normal human ocular surface microbiota contains Staphylococcus spp., Pseudomonas sp., Enterobacter sp., E. coli , and Acinetobacter sp. [ 69 , 70 ], so members of these genera have the potential to be acquired by corneal isolates of Acanthamoeba during infection. Additionally, the Acanthamoeba microbiome may originate from the external environment before colonizing human eye.…”
Section: Discussionmentioning
confidence: 99%
“…The normal human ocular surface microbiota contains Staphylococcus spp., Pseudomonas sp., Enterobacter sp., E. coli , and Acinetobacter sp. [ 69 , 70 ], so members of these genera have the potential to be acquired by corneal isolates of Acanthamoeba during infection. Additionally, the Acanthamoeba microbiome may originate from the external environment before colonizing human eye.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies suggest that the ocular surface microbiota is associated with ocular health (80,81), and that a healthy ocular microbiota may provide resistance against colonization from infectious agents (82,83). While the association of the ocular microbiota with IBK is yet to be determined, a recent study revealed a relative greater abundance of Moraxella spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bovine ocular microbial community is a potential new target for manipulation, due to diseases such as IBK (79), which is a significant health issue affecting the beef cattle industry. Human studies suggest that the ocular surface microbiota is associated with ocular health (80, 81), and that a healthy ocular microbiota may provide resistance against colonization from infectious agents (82, 83). While the association of the ocular microbiota with IBK is yet to be determined, a recent study revealed a relative greater abundance of Moraxella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been reported that S. epidermidis can cause infections such as conjunctivitis, blepharitis, corneal ulcers, and endophthalmitis, in addition to being one of the species frequently isolated from external ocular infections [36][37][38][39]. It is important to consider that every healthy person has ocular surface microbiota, which can vary according to age, environment, and geographic location, among others [2,40,41].…”
Section: Discussionmentioning
confidence: 99%